Gestión de recuperación de cartera vencida de la Compañía Agrícola Eslabón del Agro del cantón Urdaneta - Veloz León, Patricio Galo (2020)
The present case study is developed in order to know what are the causes of a very high past due portfolio in the Eslabón del Agro company, in the same way that it is analyzed in what percentage or amount the portfolio has been recovered, this case This study is carried out using the research subline, Administrative Management Model, because the detected problem covers the administrative sphere in the portfolio administration area and also the low performance of its collaborators. In order to acquire more information and to know the causes of the problem in the Eslabón del Agro company, the interview was used as a study technique, which at the time of applying it was used as an instrument the questionnaire of questions that was made to the head of the financial department, to In order to be able to provide a credit to a client, in the first place, they must carry out a study of it to know its economic stability and availability of payment and to set a certain term that must be complied with in order not to proceed to the legal field.